Efficacy of a Telehealth Parent Training Intervention for Children with Autism Spectrum Disorder: Rural versus Urban Areas. Issue 1 (2nd January 2022) - Dahiya, Angela V.; Ruble, Lisa; Kuravackel, Grace; Scarpa, Angela
ABSTRACT: Parent-mediated interventions are increasingly described in the current literature, and although parents of children with autism spectrum disorder (ASD) face many challenges in regards to behavioral concerns, there are few parent-mediated interventions that target behavioral problems. There are even fewer that are evaluated for use in rural communities where service access is limited. As such, telehealth-based interventions can be effective in addressing the unmet needs in rural areas. COMPASS for Hope (C-HOPE) is an 8-week parent-mediated intervention that enhances parent competency and reduces parent stress and child problem behavior in children with ASD. In this treatment, parent behavior management and competency are essential to determine the efficacy of C-HOPE. The purpose of this study was to compare the outcomes of telehealth-implemented C-HOPE for rural (n = 12) versus urban (n = 8) parents of children with ASD (3–12 years old) with a focus on parent competency, knowledge, and activation, as well as child problem behaviors. Significant effects were noted in each area. Future directions for telehealth in this population are discussed.